Designing of Portable Long Duration HRV Recorder - R. Krishna kumar, A. Kingsly Jabakumar, S. Syed Althaf, J. Saranraj, T. Arun, U. Rujeyanthi (Mathematical Statistician and Engineering Applications, 2023)
In the modern health scenario, prevention of disease is emphasized much rather than post-treatments. Certain life-threatening diseases like Cardiovascular disorders can be avoided, if found earlier. ECG is used to assess the heart rhythm, through which abnormalities such as poor electrical conduction and chest enlargement can be detected. The ECG waveform provides information about the heart rhythm and blood flow throughout the body. The electrodes used in ECG device can produce normal or abnormal waveform pattern. From the abnormal patterns, various heart diseases such asbachycardia, tachycardia, stroke syncope, premature contractions etc. can be diagnosed. The long duration ECG records the ECG signal of the patient continuously throughout the day, which can be stored and examined laterby the physician. In this work, recording of ECG was carried out using surface electrodes, which were connected with the instrumentation amplifier AD624, followed by the filter circuit. The obtained ECG signal is then given to ATMEGA 328p Arduino, which can be used to measure heart rate. The storage of the heart rate data can be done with the help of an SD card by interfacing Arduino board with SD card module.